Analisis Tren Kekinian Strategi dan Preferensi Orang Tua dalam Memilih Sekolah Dasar bagi Anak melalui Sistem Inden di Kota Solo - Prihanto, Prihanto; Rahmatika, Rahmatika; Nugroho, Yusuf Cahyo; Agviandra, Alfirdous Geraldi; Wulan, Nawang (Universitas Nusantara PGRI Kediri, 2026)
This research was driven by a long-standing problem and the high number of students enrolling in private, face-to-face elementary schools. The purpose of this study was to examine parents' strategies and expectations in choosing an elementary school for their children to ensure an ideal education. This study used a qualitative approach with a case study method. Data analysis was conducted using source triangulation. The data analysis technique used a synchronization between the ideal school selection strategy for children and Talcott Parsons' structural-functional theory. The results showed that Adaptation (A) is reflected in parents' motivation and expectations for their children's education. Goal Attainment (G) is reflected in parents' considerations of school quality and available facilities. Integration (I) is reflected in parents' perceptions of their children and their educational needs. Latency (L) reflects parents' trust in the school and its education system. The survey results showed that the main factors considered by parents were teacher quality and school reputation, with 86.6% and 70%, respectively, rating these factors as very important. Facilities, location, and educational costs were also important considerations. Recent trends and their influence are beginning to be noticed, albeit to a slightly lesser extent. In general, parents prioritize school quality and reputation when choosing a school for their children.